#Gejayan memanggil Sebagai Komunikasi Sosial Gerakan Mahasiswa - Hidayah, Yayuk; Trihastuti, Meiwatizal; Romlah, Oom Yomi; Adha, Muhammad Mona; Aulia Ulfah, Risti (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
This article discusses #Gejayan as asocial communication of the student movement in Yogyakarta, Indonesia. #Gejayanmemanggil became a trending topic that contributed to the call of the GejayanMemanggilactionIn the context of this discussion, there are two things to emphasize: the theme that appears in the #Gejayanmemanggil tweet and the extent of  its contribution to the organization of the demonstration. The results of the study found that the narrative theme in the #Gejayanmemanggil tweet was on in accordance with the actual conditions at that time, including the response to the Draft Criminal Code (RKUHP), changes to the Corruption Eradication Commission (KPK) Law, and various environmental issues. The contribution of #Gejayanmemanggil to the demonstration in question is defined by how it assisted in the success of the overall event.